Studi Ihwal Kurikulum, Guru, Dan Sarana Pembelajaran Bahas Arab Dalam Perspektif Perencanaan Bahasa - Tsara Aliya Salsabila (Taqdir, 2021)
Abstract This study aims to determine the policies of teaching Arabic in SMA Negeri 11 Bandung and the understanding of teachers in realizing these teaching policies to students. The method used is descriptive qualitative with a case study research design. Participants in this study were two Arabic teachers and one vice principal in the curriculum field. The instruments used were interviews and documentation. The results of this study indicate that Arabic language teaching policies at SMA Negeri 11 Bandung, namely the opening of Arabic language classes studied by language classes and cross-interest classes, curriculum, materials or teaching materials used in accordance with Permendikbud Number 37 of 2018 concerning Core Competencies and Basic Competencies in the 2013 curriculum, and the learning resources used are Arabic books for MGMP Arabic in West Java Province and Arabic books from the Ministry of Education and Culture, Larangan Dian Artha Dina Ratu. The Arabic teacher has made it happen in the learning process, meaning that the teacher has understood the teaching policies. Keyword: Curriculum, Teacher, Language Planning